Peripheral Anterior Chamber Depth and Angle Measurements Using Pentacam After Implantation of Toric and Non-toric Implantable Collamer Lenses - Zhao, Jiao; Zhao, Jing; Yang, Wen; Miao, Huamao; Niu, Lingling; Shang, Jianmin; Wang, Xiaoying; Zhou, Xingtao (Frontiers in Medicine, 2021)
Purpose: To evaluate the characteristics of peripheral anterior chamber measurements by Pentacam after posterior implantable collamer lenses (ICL) and toric ICL (TICL) with central hole (V4c) implantation. Methods: Prospective, non-randomized consecutive case series. Forty-six patients undergoing ICL implantation in one eye (Group A) and identically sized TICL in the contralateral eye (Group B) in the Refractive Surgery Center of Eye and ENT Hospital of Fudan University were prospectively included. According to ICL/TICL size, these eyes were further divided into four subgroups. Peripheral anterior chamber depth (PACD) and angle (ACA) in nasal and temporal sides were measured using Pentacam pre-operatively and 12-month post-operatively. Results: The safety indices were 1.34 ± 0.32 and 1.25 ± 0.16 and the efficacy indices were 1.20 ± 0.24 and 1.19 ± 0.19 for ICL and TICL groups, respectively. There was no significant difference in pre-operative PACD or ACA between the two groups. Post-operative PACD and ACA were significantly lower than pre-operative values. Variations of PACD and ACA of TICL group were significantly larger than those of ICL group. The change of ACA for 13.2 mm lenses was significantly larger than that of 12.6 mm lenses. Pre-operative CACD and vault were significantly associated with post-operative PACD, while pre-operative ACA and vault were significantly associated with post-operative ACA. Conclusions: Variations of PACD and ACA were greater in eyes after TICL (V4c) implantation compared with identically sized ICL (V4c) implantation and with larger size than smaller size lens implantation. Pre-operative anterior chamber structure and vault affect post-operative PACD and ACA.